PERBANDINGAN KARAKTER TOKOH UTAMA WANITA NOVEL CINTA SUCI ZAHRANA KARYA HABIBURRAHMAN EL SHIRAZY DENGAN NOVEL MATARAISA KARYA ABIDAH EL KHALIEQY - Lismarni Lismarni; Nurizzati Nurizzati; Muhammad Ismail Nasution (Jurnal Bahasa dan Sastra, 2013)
The purpose of this article is to: (a) to describe of herself character in the Novel Cinta Suci Zahrana by Habiburraman El Shirazy and Novel Mataraisa by Abidah El Khalieqy, (b) to describe of same and different of herself character Novel Cinta Suci Zahrana by Habiburraman El Shirazy and Novel Mataraisa by Abidah El Khalieqy. The source  of this study is herself unsure in the Novel Cinta Suci Zahrana by Habiburrahman El Shirazyand Novel Mataraisa by Abidah El Khalieqy. Technic of analyze is done with the descriptive theory. The find of study is the same character of herself in the Novel Cinta Suci Zahrana by Habiburrahman El Shirazy with Novel Mataraisa by Abidah El Khalieqy is : (a) hard worker, (b) like of challenge, (c) like by some people, (d) it has not like of itself. The different of herself character in the Novel Cinta Suci Zahrana by Habiburraman El Shirazy and Novel Mataraisa by Abidah El Khalieqy is: (a) the differnt of education, (b) the different of life, (c) the different to find of soulmate, (d)  the different of faced problem, (e) the different of others faced.